Solubility of naftopidil in pure and mixed solvents at 273.15–313.15 K and its correlation with the Jouyban-Acree and CNIBS/R-K models. (June 2020) - Li, Rongrong; Tang, Tian; Yin, Xianfang; Yao, Lusha; Lin, Zhipeng; Zhang, Lin; Gao, Xin; Xu, Xiaojing; Zhao, Jia; Han, Deman
Graphical abstract: Highlights: Research the dissolution behavior of naftopidil in pure and mixed solvents. Extended Hildebrand Solubility Approach was used to explain co-solvence phenomenon. The solubility data were correlated by some thermodynamic models. Some apparent thermodynamic properties were evaluated. Abstract: The dissolution behavior of naftopidil in methanol, ethanol, ethyl acetate, toluene, acetone, acetonitrile and two mixtures of (ethyl acetate + methanol) and (ethyl acetate + ethanol) was studied. In pure and mixed solvents, the solubility was determined experimentally and correlated by some thermodynamic models. The maximum data was obtained at 313.15 K in toluene, and the minimum data was obtained at 273.15 K in acetonitrile. Moreover, there is co-solvence phenomenon in two co-solvent mixtures, the values increased monotonically with the increasing temperature, while increased with increasing co-solvent (ethyl acetate) mass fraction ( w ) to a maximum value at w  = 0.8 and then decreased. The dissolution behavior of naftopidil in pure was explained by the properties of solvents such as the hydrogen bond acidity, hydrogen bond basicity, dipolarity/polarizability, and it was evaluated by Extended Hildebrand Solubility Approach in mixed solvents. Besides, the apparent dissolution standard enthalpy ( Δ H sol o ), apparent molar standard Gibbs energy ( Δ G sol o ) and apparent dissolution standard entropy ( Δ S sol o ) of naftopidil in pure and mixed solvents were also calculated.